Adverse Cardiovascular Effects of Anti-COVID-19 Drugs - Liu, Dongling; Zeng, Xiang; Ding, Zufeng; Lv, Fenghua; Mehta, Jawahar L.; Wang, Xianwei (Frontiers in Pharmacology, 2021)
Abstract Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) or COVID-19 infection is the cause of the ongoing global pandemic. Mortality from COVID-19 infection is particularly high in patients with cardiovascular diseases. In addition, COVID-19 patients with preexisting cardiovascular comorbidities have a higher risk of death. Main cardiovascular complications of COVID-19 are myocardial infarction, myocarditis, acute myocardial injury, arrhythmias, heart failure, stroke, and venous thromboembolism. Therapeutic interventions in terms of drugs for COVID-19 have many cardiac adverse effects. Here, we review the relative therapeutic efficacy and adverse effects of anti-COVID-19 drugs.